Antibacterial activity of mangosteen (garcinia mangostana linn.) leaf ethanol extract against oral pathogenic bacteria: a laboratory experimental study - Rahmawati, Dicha Yuliadewi; Arron, Yabest; Bitik, Alexander; Hadinata, Michael; Naliani, Silvia; Aiumdee, Prashyaneeyasak; Sugiaman, Vinna Kurniawati (Padjadjaran Journal of Dentistry, 2026)
Introduction: Nature-based medicines are multi-component agents that work in a multi-targeted manner with minimal side effects. Mangosteen leaves (Garcinia mangostana L.) contain flavonoids, tannins, and saponins that serve as antibacterial agents. This research aimed to analyze alternative agents to chlorhexidine mouthwash derived from natural ingredients. Methods: This laboratory experimental study observed the inhibition zone diameters of mangosteen leaf ethanol extract at concentrations ranging from 3.125% to 100% against P. gingivalis, A. actinomycetemcomitans, and S. sanguinis using the disc diffusion method. One-Way ANOVA followed by Tukey HSD tests were used to analyze the statistical differences among the bacterial groups across all concentrations. Results: The 100% concentration exhibited the largest inhibitory zones: 14.78 ± 0.60 mm for P. gingivalis, 11.08 ± 0.02 mm for A. actinomycetemcomitans, and 10.55 ± 0.48 mm for S. sanguinis. One-Way ANOVA and Tukey HSD tests showed a p-value of 0.000, indicating a significant antibacterial effect against P. gingivalis, A. actinomycetemcomitans, and S. sanguinis. Conclusion: Ethanol extract of mangosteen leaves (Garcinia mangostana L.) exhibits significant antibacterial activity, with the highest inhibitory effect observed at a 100% concentration.